2020
DOI: 10.21037/tau-20-615
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of conventional versus advanced pelvic floor muscle training in the management of urinary incontinence after radical prostatectomy: a systematic review and meta-analysis of randomized controlled trials

Abstract: Background: The underutilization of additional supportive muscles is one of the potential reasons for suboptimal efficacy of conventional pelvic floor muscle training (CPFMT). The present study concentrates on any advantage of advanced pelvic floor muscle training (APFMT) in patients with urinary incontinence (UI) after radical prostatectomy (RP). Methods: Literature search was conducted on PubMed, Embase, Cochrane Library and Web of Science from database inception to February 2020. The data analysis was perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 43 publications
0
23
0
Order By: Relevance
“…On a global scale, the agestandardized incidence rate of PCA increased from 30.5 cases per 100,000 population in 1990 to 37.9 cases per 100,000 population in 2017, which is positively related to the sociodemographic index in most regions (2). The PCA incidence has been increasing in most Asian countries, ranking first in Chinese men regarding its incidence and mortality among all urologic tumors (1,3). This increase might be attributed to not only increased PSA screening but also the conversion of a westernized lifestyle (4).…”
Section: Introductionmentioning
confidence: 99%
“…On a global scale, the agestandardized incidence rate of PCA increased from 30.5 cases per 100,000 population in 1990 to 37.9 cases per 100,000 population in 2017, which is positively related to the sociodemographic index in most regions (2). The PCA incidence has been increasing in most Asian countries, ranking first in Chinese men regarding its incidence and mortality among all urologic tumors (1,3). This increase might be attributed to not only increased PSA screening but also the conversion of a westernized lifestyle (4).…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, a previous review showed the increased trend of incidence of metastatic PCA from 2007 to 2013, and the greatest increment was seen in men aged 55-69 years (92% increase from 2004 to 2013) [36]. Management of PCA currently includes surgery, radiotherapy and hormone therapy [4]. Immunotherapy for PCA patients has emerged in recent years, which has been demonstrated to be effective for other tumours, such as metastatic melanoma, renal and lung cancer [37].…”
Section: Discussionmentioning
confidence: 99%
“…The treatment modalities of PCA mainly consist of observation (active surveillance or watchful waiting), local curative treatment (RP or radical radiotherapy), and hormone therapy, depending on age, tumour stage, presence of metastasis and patient performance and reference [4]. Observation is the most effective choice for low-risk PCA patients aged 65-75 years [6]; however, about 30% of patients with intermediate or high-risk localized and locally advanced cancer experience recurrence and subsequently succumb to the disease despite surgery and radiation [7,8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kegel's exercises, first proposed in 1948 for post-partum incontinence 11 have been proving their efficacy in many studies on male patients. [12][13][14] They consist in voluntary contractions of the pelvic muscles, aimed to strengthen them (especially the pubococcygeus) and improve their endurance. The goal is to use the muscular group called 'levator ani' to help the sphincter constrict the urethra.…”
Section: Introductionmentioning
confidence: 99%